The Impact of Law No. 6 of 2023 on Job Creation on Foreign Investment Policy in Indonesia - Iftina Cahyanda Putri Aimee; Sang Ayu Putu Rahayu; Duhita Driyah Suprapti (Anthroposia: Journal of Social and Human Development, 2026)
This study examines the impact of Law No. 6 of 2023 concerning Job Creation on foreign investment policy in Indonesia through a normative juridical approach. The research employs statutory and conceptual analyses of primary legal materials, including the Constitution of the Republic of Indonesia of 1945, Law No. 25 of 2007 on Investment, and Law No. 6 of 2023, complemented by scholarly literature on investment governance and international investment law. The findings indicate that the Job Creation Law restructures Indonesia’s investment framework by strengthening regulatory coherence, enhancing legal certainty, expanding investment opportunities, and improving investment facilitation mechanisms. The reform contributes to greater regulatory predictability and supports foreign investor confidence through a more integrated investment regime. The analysis further demonstrates that investment liberalization remains subject to constitutional economic principles that preserve state regulatory authority in matters relating to public welfare, environmental sustainability, labor protection, and the development of micro, small, and medium enterprises. The study concludes that the long term effectiveness of Indonesia’s foreign investment policy depends on maintaining a balanced relationship between investment facilitation objectives and regulatory sovereignty within the framework of sustainable national development.